1993
DOI: 10.1111/j.2042-7158.1993.tb05630.x
|View full text |Cite
|
Sign up to set email alerts
|

Emulsified Perfluorochemicals as Respiratory Gas Carriers: Recovery of Perfluorodecalin Emulsion Droplets from Rat Tissues

Abstract: To further understand the in-vivo biokinetic behaviour of perfluorochemical (PFC) emulsions, male rats were injected (10 mL kg-1) with 30% (w/v) emulsified perfluorodecalin (FDC) and uptake into tissues assessed. At 72 h after injection, the mean (+/- s.e.m.) diameters of FDC droplets recovered from liver and spleen were 2.24 +/- 0.04 and 2.78 +/- 0.10 microns, respectively; droplets recovered from lung after 72 h (mean: 1.73 +/- 0.13 micron) were significantly smaller (P < 0.01). After 7 days, FDC droplet dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…PFC liquids injected intravascularly consist of an emulsion of 80-to 500-nm droplets as oxygen carriers. Depending on the route of injection into the body, the journey of the PFC droplets can be distinguished into four subsequent paths: intravascular transport, storage in organs (e.g., liver and spleen), transport to the lungs, and expiration from the alveolae of the lungs [8]. The vascular paths to and from storage organs are characterized by a relatively large distance between particles and a high intravascular mobility of the PFC droplets in comparison to the other paths.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…PFC liquids injected intravascularly consist of an emulsion of 80-to 500-nm droplets as oxygen carriers. Depending on the route of injection into the body, the journey of the PFC droplets can be distinguished into four subsequent paths: intravascular transport, storage in organs (e.g., liver and spleen), transport to the lungs, and expiration from the alveolae of the lungs [8]. The vascular paths to and from storage organs are characterized by a relatively large distance between particles and a high intravascular mobility of the PFC droplets in comparison to the other paths.…”
mentioning
confidence: 99%
“…Two reported mechanisms are thought to be responsible for the increase in drop size: coalescence, which means a fusion of droplets of an emulsion to a compact liquid phase, and Ostwald ripening, known from monocrystal growth in aqueous solutions, by diffusion of molecules from small to larger particles [8,10,12]. Many authors maintain that the observed increase in droplet size most probably occurs in the liver and the spleen, which are organs where the PFCs are trapped for much longer periods than in the blood or lungs [8,10]. While current theories presume that the observed increase in droplet size can be localized in these organs, the proposed models do not offer Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation